Brand Image as a Mediating Variable of the Influence of Perceived Ease of Use and Price on Customer Satisfaction - Nur Faiza; Nursani (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2023)
Customer satisfaction is important for the sustainability of businesses, both online and offline. The purpose of this research is to examine the role of brand image in mediating the relationship between perceived ease of use and price on customer satisfaction. Data was collected by distributing questionnaires to 160 respondents in East Java who had made online purchases using TikTok Shop in the last 3 months. Then, the hypotheses in this study were tested using Partial Least Squares (PLS). The research findings reveal that: (1) Perceived ease of use has a positive and significant effect on customer satisfaction; (2) Perceived ease of use has a positive and significant effect on brand image; (3) Price has a positive and significant effect on brand image; (4) Price has a positive and significant effect on customer satisfaction; (5) Brand image has a positive and significant effect on customer satisfaction; (6) Brand image is able to mediate the influence of perceived ease of use on customer satisfaction; (7) Brand image is able to mediate the influence of price on customer satisfaction.